2010
DOI: 10.1111/j.1540-6237.2010.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Religion, and Opposition to Same-Sex Marriage

Abstract: Objective. We examine racial differences in support for same‐sex marriage, and test whether the emerging black‐white gap is a function of religiosity. We explore how religious factors play a crucial role in racial differences, and how secular factors have varying effects on attitudes for whites and African Americans. Methods. Using data from the General Social Surveys, we estimate ordinal logistic regression models and stacked structural equation models. Results. We show that the racial divide is a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
181
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(200 citation statements)
references
References 42 publications
4
181
2
5
Order By: Relevance
“…Religious affiliation has also been found to impact attitudes toward sexual minorities (Sherkat, De Vries, & Creek, 2010). Among U.S. samples, negative attitudes toward LGBT people have been associated with conservative religious beliefs and attitudes (Ahrold & Meston, 2010;Sherkat et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Religious affiliation has also been found to impact attitudes toward sexual minorities (Sherkat, De Vries, & Creek, 2010). Among U.S. samples, negative attitudes toward LGBT people have been associated with conservative religious beliefs and attitudes (Ahrold & Meston, 2010;Sherkat et al, 2010).…”
mentioning
confidence: 99%
“…Among U.S. samples, negative attitudes toward LGBT people have been associated with conservative religious beliefs and attitudes (Ahrold & Meston, 2010;Sherkat et al, 2010). For example, Baiocco et al (2015) investigated a range of factors associated with parental reactions to their children coming out and found that while mothers and fathers did not have significant differences in their reactions, right-wing political conservatism and strong religious beliefs significantly predicted whether parents responded to their children's coming out in a positive or negative manner.…”
mentioning
confidence: 99%
“…In addition, a widely documented link exists between an African American voter's churchly dedication and her support for same-sex marriage (for recent evidence, read Griffith, & Cruz, 2010). More relevant to this paper, several scholars (Egan & Sherrill, 2010;Sherkat, Vries & Creek, 2010) and journalists (Besen, 2010;Grad, 2008;Roker, 2008;Silver, 2008;Wilson, 2009) discuss the impact of race on attitudes about Proposition 8 specifically.…”
Section: Religiosity As a Mediating Conceptmentioning
confidence: 99%
“…It hardly seemed fair, especially since, compared to Whites, a disproportionate number of Blacks voted to amend the state's constitution and overturn the legitimacy of same-sex marriage (Besen, 2010;Egan & Sherrill, 2009;Murray, 2009), and some believe that African-American turnout was critical to the passage of this amendment. The most conspiratorial of these claims imply that pro-Obama enthusiasm among Black voters was exploited to mobilize them against same-sex unions (Abrajano, 2010;CNN Wire Staff, 2012;Miller, 2009;Sherkat, Vries, & Creek, 2010). Such claims begged the question: "how could African-Americans, a group far too familiar with the abuses of social exclusion, vote to deny other minorities the right to equal citizenship?"…”
Section: Introductionmentioning
confidence: 99%
“…Research (Cadge, Olson & Wildeman, 2008;Sherkat, de Vries, & Creek, 2009;Van Geest, 2007) has shown Protestant, evangelical religious affiliation plays a major role in shaping individuals' attitudes about the morality of homosexuality. Adamczyk and Pitt (2009) …”
Section: Christianity and Instructional Leadership = Social Justice Lmentioning
confidence: 99%